2001
DOI: 10.1074/jbc.m102200200
|View full text |Cite
|
Sign up to set email alerts
|

Purine but Not Pyrimidine Nucleotides Support Rotation of F1-ATPase

Abstract: The binding change model for the F 1 -ATPase predicts that its rotation is intimately correlated with the changes in the affinities of the three catalytic sites for nucleotides. If so, subtle differences in the nucleotide structure may have pronounced effects on rotation. Here we show by single-molecule imaging that purine nucleotides ATP, GTP, and ITP support rotation but pyrimidine nucleotides UTP and CTP do not, suggesting that the extra ring in purine is indispensable for proper operation of this molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 19 publications
6
32
0
Order By: Relevance
“…However, given that (i) MgITP generates ␥ rotation with the same characteristics as MgATP (47), and (ii) that K d3 (MgITP) is Ϸ50-fold higher than K d3 (MgATP) (12,13), it does not seem very likely that the initial step of binding to the low-affinity site drives the rotation substep. Rather, it seems to be the subsequent conversion of low-affinity to high-affinity site, accompanied by a change in conformation of the ␤ subunit from a ''half-closed'' to the fully closed state, which makes ␥ rotate (similar as suggested in ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that (i) MgITP generates ␥ rotation with the same characteristics as MgATP (47), and (ii) that K d3 (MgITP) is Ϸ50-fold higher than K d3 (MgATP) (12,13), it does not seem very likely that the initial step of binding to the low-affinity site drives the rotation substep. Rather, it seems to be the subsequent conversion of low-affinity to high-affinity site, accompanied by a change in conformation of the ␤ subunit from a ''half-closed'' to the fully closed state, which makes ␥ rotate (similar as suggested in ref.…”
Section: Discussionmentioning
confidence: 99%
“…A mutant ␣ 3 ␤ 3 ␥ subcomplex (␣-C193S, ␤-His-10 at N terminus, ␥-S107C͞I210C) from a thermophilic Bacillus PS3 (referred to as F 1 unless otherwise specified) was expressed and purified as described (24). ATP, ADP, and phosphoenolpyruvate were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies (17)(18)(19) have indicated that the overall affinities of F 1 for MgGTP and MgITP are considerably lower than those for MgATP, while V max (hydrolysis) appeared to be less affected. Both MgGTP and MgITP are competent at eliciting rotation (19) while MgGDP and MgIDP are good substrates in ATP synthesis (17).…”
mentioning
confidence: 99%
“…Both MgGTP and MgITP are competent at eliciting rotation (19) while MgGDP and MgIDP are good substrates in ATP synthesis (17). Unfortunately, GTP has significant absorbance at 295 nm, causing a large inner filter effect in Trp fluorescence experiments.…”
mentioning
confidence: 99%